Functional connectivity when detecting rare visual targets in schizophrenia. (30th March 2017) - Jimenez, Amy M.; Lee, Junghee; Green, Michael F.; Wynn, Jonathan K.
Abstract: Individuals with schizophrenia demonstrate difficulties in attending to important stimuli (e.g., targets) and ignoring distractors (e.g., non-targets). We used a visual oddball task during fMRI to examine functional connectivity within and between the ventral and dorsal attention networks to determine the relative contribution of each network to detection of rare visual targets in schizophrenia. The sample comprised 25 schizophrenia patients and 27 healthy controls. Psychophysiological interaction analysis was used to examine whole-brain functional connectivity in response to targets. We used the right temporo parietal junction (TPJ) as the seed region for the ventral network and the right medial intraparietal sulcus (IPS) as the seed region for the dorsal network. We found that connectivity between right IPS and right anterior insula (AI; a component of the ventral network) was significantly greater in controls than patients. Expected patterns of within- and between-network connectivity for right TPJ were observed in controls, and not significantly different in patients. These findings indicate functional connectivity deficits between the dorsal and ventral attention networks in schizophrenia that may create problems in processing relevant versus irrelevant stimuli. Understanding the nature of network disruptions underlying cognitive deficits of schizophrenia may help shed light on the pathophysiology of this disorder. Highlights: Attention deficits in schizophrenia involve salience and sustained control processes. These processes are associated with ventral and dorsal brain networks, respectively. We examined functional connectivity of these networks during a visual oddball task. Patients showed reduced connectivity between the ventral and dorsal networks. The findings may explain difficulties processing relevant versus irrelevant stimuli.